Serum zinc status of neonates with seizure - Olia Sharmeen; Md. Abid Hossain Mollah; Md. Hasanur Rasbid; Shamshad B. Quaraishi (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Seizure is a common neurological disorder in neonatal age group!. Primary metabolic derangement is one of the important reason behind this convulsion during this period. Among primary metabolic derangement hypoglycemia, is most common followed by bypocalcaemia, hypomagnesaemia, low zinc status etc. As causes of many cases of convulsion remain unknown in neonate. Objectives: To see the zinc status in the sera of neonate with convulsion. So that if needed early intervention can be taken up and thereby prevent complications. Method: A total of 50 neonates (1-28 days) who had convulsion with no apparent reasons of convulsion were enrolled as cases and 50 healthy age and sex matched neonates were enrolled as controls. After a quick clinical evaluation serum zinc status was estimated from venous blood by atomic absorption method in Chemistry Division, Atomic Energy Centre. Low zinc was considered if serum value was <0.7mg/L. Results: Among a total of 50 cases 6% had low zinc value & 2% of controls also had low zinc level. The mean serwu zinc level of cases and controls were 1.57±0.95 and 2.37±1.06 mmol/1 respectively (p<0.01). Conclusion: From the study it is seen that low zinc value is an important cause of neonatal seizure due to primary metabolic abnormalities. So early recognition and treatment could save these babies from long term neurological sequelies.